Proximate Composition, Mineral Content and Secondary Metabolites of Three Medicinal Wild Fagonia Species - El-Zayat, Mustafa M.; El-Amier, Yasser Ahmed; El-Halawany, El-Sayed F.; Abo Aisha, Iman A. (Food Biology, 2020)
Proximate composition of the aerial parts of three Fagonia species (Fagonia arabica L., F. mollis Delile and F. cretica L.) collected from different habitats were analyzed. Macro- and micro-elements as well as some secondary metabolites were estimated. The obtained results revealed that F. creticus contains appreciable levels of nutritive components considering that its nutritional value (351.06 kcal/100g dry wt.) was remarkably higher than that of F. arabica and F. mollis (327.99 and 293.07 kcal/100g dry wt., respectively). The concentration of Na was relatively the highest among the other estimated macroelements in the studied species followed by K, Ca and Mg, respectively while Fe was the highest microelement followed by Cu, Mn and Zn, respectively. The phytochemical composition revealed that methanolic extract of F. creticus was the richest in total alkaloids and flavonoids, while F. arabica found to be the richest in total phenolics and tannins.